Wirausaha: Siswa MA Unggulan Tlasih berlatih kewirausahaan di madrasah - Sholihah, Tsaniyatus (Maliki Interdisciplinary Journal, 2024)
Entrepreneurship training in schools is often ignored, even though entrepreneurship is one of the supporting sectors for Indonesia to become a developed country. So it must grow patience in an educator to be able to give special attention to the entrepreneurial ability of students. With the contribution of education to the development of entrepreneurship, will provide a huge positive effect. This can be seen from the many teenagers who have dared to start learning and MSME businesses. The interest of these teenagers is a great opportunity for education and also the government to provide support so that entrepreneurship in Indonesia is getting bigger and more advanced. Thus this research will explain how important entrepreneurship is. This research uses a case study with a qualitative approach method that is done with descriptive analysis and argument from a collection of data that has been obtained through interviews as well as a collection of various literature sources such as books, articles, and school documents. this research will discuss several examples of entrepreneurial activities carried out in schools such as school corporations, honesty canteens and also entrepreneurship training in particular. This study aims to describe the results of the researcher’s analysis of the importance of entrepreneurial activities in schools.